Gemcitabine Cisplatin and Durvalumab Experience in Advanced Biliary Tract Cancers: A Real-World, Multicentric Data From India - Vamshi Krishna Muddu; Anjali Shah; Anupa John; Abhishek Raj; Ankur Bahl; Senthil J. Rajappa; Thirumalairaj Raja; Joydeep Ghosh; Viraj Lavingia; Amish Vora; Prabhat Bhargava; Anant Ramaswamy; et al. (JCO Global Oncology)
PURPOSEBiliary tract cancers (BTCs) are usually diagnosed in advanced stages, where treatment options are either palliative chemotherapy and/or best supportive care. The breakthrough results of the TOPAZ-1 trial demonstrated a 24% decrease in risk of death at 2 years with the addition of durvalumab to chemotherapy.MATERIALS AND METHODSThis was a multicenter retrospective cohort study conducted across 14 institutions in India. All the patients were diagnosed with advanced BTCs. The primary objective was to assess median overall survival (mOS) with the use of durvalumab in combination with chemotherapy backbone. The patient details, treatment details, laboratory results, and outcome parameters were recorded from the prospectively collected databases.RESULTSA total of 148 patients were included with a median age of 57.5 years; 36 (24.3%) patients had borderline Eastern Cooperative Oncology Group performance status ≥2. The most common subtype was gall bladder cancer (GBC), seen in 94 patients (63.5%); 126 (85.1%) patients presented with de novo metastases. At a median follow-up of 6.8 months (95% CI, 5.9 to 7.8), the estimated mOS for the entire cohort was 12 months (95% CI, 7.8 to 16.3) and median progression-free survival was 8.2 months (95% CI, 7.1 to 9.4) with objective response achieved in 44 (29.7%) patients, and the estimated 2-year OS being 25%. Immune-related grade 3/4 adverse events were reported in 11 (7.4%) patients. In multivariate analysis, age <60 years (P = .001) and standard dose of durvalumab (P < .001) were found to have improved OS compared with age >60 years and low dose of durvalumab.CONCLUSIONTo our knowledge, these real-world data provide the first evidence in Indian context of the efficacy and safety of durvalumab plus chemotherapy in patients with advanced/metastatic BTCs especially in GBC.